2020
DOI: 10.1103/physreva.102.033523
|View full text |Cite
|
Sign up to set email alerts
|

Observation and analysis of creation, decay, and regeneration of annular soliton clusters in a lossy cubic-quintic optical medium

Abstract: We observe and analyze formation, decay, and subsequent regeneration of ring-shaped clusters of (2+1)dimensional spatial solitons (filaments) in a medium with cubic-quintic (focusing-defocusing) self-interaction and strong dissipative nonlinearity. The cluster of filaments, which remains stable over ≈17.5 Rayleigh lengths, is produced by the azimuthal modulational instability from a parent ring-shaped beam with embedded vorticity l = 1. In the course of still longer propagation, the stability of the soliton cl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…Diffraction, nonlinear refraction, and nonlinear loss of the switch beam must be considered within the framework of the continuous wave model. If liquid CS2 is excited using the femtosecond pulses with peak intensities of up to hundreds of GW/cm2, it behaves as a cubic-quintic (focusing-defocusing) refractive medium 12 . Furthermore, we describe the nonlinear losses associated with multiphoton absorption and light scattering in CS2 using a theoretical wave-coupled model 13 .…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Diffraction, nonlinear refraction, and nonlinear loss of the switch beam must be considered within the framework of the continuous wave model. If liquid CS2 is excited using the femtosecond pulses with peak intensities of up to hundreds of GW/cm2, it behaves as a cubic-quintic (focusing-defocusing) refractive medium 12 . Furthermore, we describe the nonlinear losses associated with multiphoton absorption and light scattering in CS2 using a theoretical wave-coupled model 13 .…”
Section: Theorymentioning
confidence: 99%
“…For the liquid CS2, n=1.606, n2=2.1×1015 cm2/W, and n4 =2.0×1027 cm2/W2 12 . The extinction coefficient αNL, which indicates nonlinear losses, is expressed intensity-dependently as αNL=αexp[(|Eswitch|2Ith)/Iδ]exp(Ith/Iδ)Ith/Iδ+exp[(|Eswitch…”
Section: Theorymentioning
confidence: 99%
“…The CQ terms may be similarly induced by a sample of an optical material combining the self-focusing and defocusing cubic and quintic nonlinearities, whose absorption is low enough to be neglected. This may be, as mentioned above, carbon disulfide in the liquid form, which was used for the creation of stable (2+1)-dimensional spatial solitons [80], quasi-stable (2+1)-dimensional optical solitons with embedded vorticity [81], and, very recently, of quasi-stable necklace arrays of optical beams with imprinted vorticity [20]. Another appropriate CQ material is a colloidal suspension of metallic nanoparticles, in which strengths of cubic and quintic nonlinearities may be accurately adjusted by selecting the size and concentration of the particles [82].…”
Section: The Model and Fundamental Solitonsmentioning
confidence: 99%
“…In particular, the creation of nearly stable necklace patterns with imprinted overall vorticity in a medium with the cubic-quintic (CQ) nonlinearity (liquid carbon disulfide) was very recently reported in Ref. [20].…”
Section: Introductionmentioning
confidence: 98%
“…High-order nonlinearity like the quintic nonlinear term [14,15,16,17] also exists in dense media or for high density wave propagation, the combination of which with cubic nonlinearity forms the cubic-quintic (nonlinearity) media [18,19,20,21,22,23], where the high-order nonlinear term takes the self-defocusing, while the cubic term can be either self-focusing or self-defocusing [24,25,26,27,28]. It should be pointed out that, in two-and three-dimensional models, the competing cubic-quintic nonlinearity of the media can stabilize more complicated wave structures including the multidimensional solitons and their vortical ones (the solitons with embedded vorticity) [25,29,30], ring-shaped soliton clusters [31]. In addition, theoretical predictions [32,33] and experimental confirmations [34,35,36] have demonstrated that the competing nonlinear terms, arising from meanfield term (atom-atom collisions) and beyond-mean-field term (quantum fluctuations) named by Lee-Huang-Yang quantum corrections [37,38,39], in the context of two-component Bose-Einstein condensates (BECs) could give rise to stable matter wave states called quantum droplets from one to three dimensions.…”
Section: Introductionmentioning
confidence: 99%